Non-indigenous polychaetes along the coasts of Italy: a critical review - LANGENECK, JOACHIM; LEZZI, MARCO; DEL PASQUA, MICHELA; MUSCO, LUIGI; GAMBI, MARIA CRISTINA; CASTELLI, ALBERTO; GIANGRANDE, ADRIANA (Mediterranean Marine Science, 2020)
Non-indigenous species (NIS) represent one of the most relevant threats to biodiversity, ecosystem functioning and human activities, and their occurrence and spread have been the subject of numerous works and revisions. However, the information available is rather confused for several taxa, including polychaetes, which are characterised by having a high number of cryptogenic and questionable species. This work aims at providing a revised checklist of alien polychaetes occurring along the coasts of Italy, based on the examination of newly collected and deposited material and on the critical analysis of published and gray literature, and whenever possible on the re-examination of historical material. Of the 86 polychaete species reported as NIS in Italian waters, 25 are confirmed as alien species, while 3 are cryptogenic, and 40 should be considered questionable. Finally, 18 species were excluded from non-indigenous species checklists, either because they are native, or because they represent misidentifications of other species. The high number of cryptogenic and questionable species points at the need of molecular studies and taxonomic revisions for the majority of polychaete taxa reported as NIS, in order to clarify their taxonomy, origin, introduction pathways and spreading patterns.